The dark side of the vote biased voters, social information, and information aggregation through majority voting - Morton, Rebecca B. 1954-; Piovesan, Marco; Tyran, Jean-Robert 1967- (Discussion paper, 2013)
We experimentally investigate information aggregation through majority voting when some voters are biased. In such situations, majority voting can have a "dark side", that is, result in groups making choices inferior to those made by individuals acting alone. In line with theoretical predictions, information on the popularity of policy choices is beneficial when a minority of voters are biased, but harmful when a majority is biased. In theory, information on the success of policy choices elsewhere de-biases voters and alleviates the inefficiency. However, in the experiment, providing social information on success is ineffective and does not de-bias voters.